MODALIZATION IN HEALTH PUBLIC SERVICE ADVERTISEMENT: A SYSTEMIC FUNCTIONAL GRAMMAR STUDY - Ponia Mega Septiana; Imam Muhtadi; Wiwi Sari (Prologue: Journal on Language and Literature, 2024)
Using a systemic functional grammar approach, this research looks for modalization in health public service announcements. A descriptive qualitative method is used in this study. A component of modality that is elaborated in interpersonal Meta function, known as "modalization," expresses the writer's or speaker's opinions about the material being communicated. Various media types are available for the acquisition of information. One of them might be an advertising campaign. It can be accessed online, in periodicals, and on television. This writer uses the Systemic Functional Grammar technique to examine the health public service announcement. The modalization employed in health public service announcements is the subject of the current writer's analysis. Pinterest provides health public service announcements, which is where the research's data came from.